Defense Strategy of Religious, Pancasila, and National Culture in Indonesian School and Indonesian Diaspora as Anti-Radicalism Efforts - Sofyan, Ahmad; Misriandi, Misriandi; Lesmana, Johan Aristya (Journal of Education and Training, 2022)
This study aims to analyze the strategy of the Republic of Indonesia Embassy through the management of Indonesian Schools and diaspora in maintaining religious values, archipelago cultural treasures, and Pancasila values. This research was carried out based on the phenomenon that the Indonesian Foreign School (SILN) had planted religious values, in Pancasila and promoted the culture of the archipelago, but the diaspora preferred to live abroad. In addition, the issue of the tendency for radical religious understanding was also a concern for SILN students and the Indonesian diaspora in Malaysia, Saudi Arabia, and the Netherlands as representatives of the Asian, African and European regions. This study uses descriptive qualitative methods the data was collected from diaspora representatives, the head of the Indonesian School, Indonesian School students, and the Indonesian Ministry of Foreign Affairs, while in-depth interviews, questionnaires, and observations were made of the 3 countries. The purpose of the results of this study was to map the suitability of the curriculum with the local environment from the dimensions of religion, Pancasila, and archipelago culture. In the future, the government not only organizes Indonesian Schools Abroad but also Indonesian Madrasas Abroad (MILN) to increase moderate religious values that are not affected by radicalism activities and provide distinctive characteristics of the archipelago culture and are characterized by Pancasila.